Peculiarities of particles and field dynamics at critical intensity of electromagnetic waves (Part I) - Buts, V.A. (Вопросы атомной науки и техники, 2005)
Some results of study of the charged particles that are moving in a field of intensive electromagnetic waves are represented. The integrals are investigated and some schemes of laser acceleration are considered. It was revealed that the most effective scheme of acceleration is the scheme, in which the laser pulse with circular polarization is used. Is shown that the forces of radiating friction can promote transferring of energy from a laser field to particles. Besides is shown, that for laser acceleration the force of radiating friction are considerably less essential, than in cyclic accelerators. Викладено деякі результати вивчення динаміки заряджених часток у полі інтенсивних електромагнітних хвиль. Досліджено інтеграли і розглянуто деякі схеми лазерного прискорення. Показано, що найбільш ефективною схемою прискорення є схема, у якій використовується лазерний імпульс із круговою поляризацією. Показано, що сили радіаційного тертя можуть сприяти передачі енергії від лазерного поля до часток. Крім того, показано, що для лазерного прискорення сили радіаційного тертя значно менш істотні, ніж у циклічних прискорювачах. Изложены некоторые результаты изучения динамики заряженных частиц в поле интенсивных электромагнитных волн. Исследованы интегралы и рассмотрены некоторые схемы лазерного ускорения. Показано, что наиболее эффективной схемой ускорения является схема, в которой используется лазерный импульс с круговой поляризацией. Показано, что силы радиационного трения могут способствовать передаче энергии от лазерного поля к частицам. Кроме того, показано, что для лазерного ускорения силы радиационного трения значительно менее существенны, чем в циклических ускорителях.